Integer ambiguity Resolution in Multi-constellation GNSS for LEO Satellites POD - Wang, Kan; El-Mowafy, Ahmed; Yang, Xuhai (2023)
Precise Orbit Determination (POD) of Low Earth Orbit (LEO) satellites is essential for future LEO-augmented Positioning, Navigation and Timing (PNT) service based on the use of Global Navigation Satellite Systems (GNSS) measurements. Compared with the ambiguity-float LEO satellite POD, Integer Ambiguity Resolution (IAR) reduces number of parameters, eliminates the high correlations between the ambiguities and other estimable parameters, and strengthens model strength. In this study, using real data from Sentinel-6A tracking dual-frequency GPS and Galileo observations, the wide-lane (WL) and narrow-lane (NL) ambiguity fixing rates and the effects of the IAR on orbital accuracy are assessed in the single- and dual-constellation scenarios. Post-processed high-accuracy GNSS satellite clocks, orbits and Observable-specific Signal Biases (OSBs) from the final products of the Center for Orbit Determination in Europe (CODE) and the rapid products of the GeoForschungsZentrum (GFZ) are used for the analysis. Results showed that both the WL and NL fixing rates in the Galileo-only scenario are higher than those in the GPS-only scenario, reaching more than 98%. This implies a better signal quality of the Galileo observations. Applying IAR has improved the orbital accuracy for all single- and dual-constellation scenarios, and was shown to be especially helpful in reducing the once-per-revolution systematic effects in the along-track orbital errors, with over 50% improvement when using the COM products. With the IAR enabled, when using the COM final products, the 3D RMS of the orbital errors amounts to 1.2, 1.2 and 1.1 cm in the GPS-only, Galileo-only and GPS+Galileo combined scenarios, and the RMS of the Orbital User Range Errors (OUREs) amounts to 0.7, 0.7 and 0.6 cm, respectively. When using the GFZ rapid products, the IAR-enabled 3D RMS were 1.8, 2.1 and 1.4 cm in the GPS-only, Galileo-only and GPS+Galileo combined scenarios, with OURE RMS of about 1 cm.